How Banking Competition changed over Time - Jacob A. Bikker; Laura Spierdijk (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2008)
This paper is the first detailed and world-wide investigation of the developments in banking competition during the past fiffteen years. Using the Panzar-Rosse approach, we establish significant changes over time in the competitiveness of the banking industry. The changes in competition over time are small on average, but substantial for several countries and regions. Various Western economies faced a significant decline in banking competition during recent years. In particular, the competitive climate in the euro area was subject to a major break around 2001 - 2002, initiating a period of less competition. Also for the United States and Japan we establish a break during this period. The part of Eastern Europe that now belongs to the European Union experienced a significant but modest decrease in competition during the past ten years. Furthermore, the banking industry in emerging markets became more competitive during the last decade. We attribute the predominantly downward trend in competition to increased bank size and the shift from traditional intermediation to off-balance sheet activities.
Keywords: 330; competition; banking industry; Panzar-Rosse model; structural breaks